The Meta-analysis: laparoscopy versus open distal gastrectomy for advanced gastric cancer - Jian Wang (临床与病理杂志, 2026)
Objective: In this study, using meta-analysis, we compared the LADG with open distal gastrectomy (ODG) in the treatment of patients with advanced gastric cancer. Methods: The RevMan 5.0 software was used for the meta-analysis. Results: The meta-analysis indicated that in comparison with patients who underwent open distal gastrectomy, patients who were treated with LADG had shorter hospital stay, less analgesic requirements and blood loss, less overall complications, including intestinal obstruction, earlier time to liquid ingestion, and less wound infections. Nevertheless, there is no significant difference between LADG and ODG in anastomotic hemorrhage, anastomotic stenosis, duodenal stump leakage, tumor margin, lymph node dissection, mortality, pneumonia or reoperation. And in case of long-term survivals, both OS (overall-survival) and DFS (disease-free survival) showed no significant difference between LADG and ODG. Conclusion: LADG is feasible for the treatment of advanced gastric cancer, and provides several advantages.